KREASI TEKNIK PATCHWORK DARI KAIN BATIK DAN LURIK PADA BUSANA PESTA ANAK WANITA - Rosma Roida Sihotang; Titin Prihatini (Jurnal Socia Akademika, 2022)
The purpose of this research: 1) Want to see the suitability of the women's party dress model from batik and lurik fabrics with patchwork techniques.2) Want to see the harmony of colors and motifs of the combination of batik and lurik fabrics in women's party clothes with patchwork techniques. 3) Want to know the total looks of women's party clothing products from batik and lurik fabrics with patchwork techniques. The research method used is the 1) R&D development method, 2) FGD (Focus Group Discussion), 3) Documentation. With the research subject of batik cloth, lurik, and the object of research is the application of patchwork techniques. Analysis of the data used is descriptive interpretive data analysis to describe the data to be obtained in the field related to the subject matter. The results showed that the descriptive results of the level of suitability of the fashion model on the results of the model I test respondents said 42.8% very suitable, 57.1% suitable, the results of the model II test respondents said 57.1% very suitable, 42.8% suitable and the results of the model III test respondents said 57.1% very suitable and 42.8% suitable. The suitability of color and motif combinations in the test results of model I respondents said 57.1% was very compatible, 42.8% matched, the results of model II test respondents said 57.1% was very compatible, 42.8% matched and the results of model III test respondents said 42.8% very compatible, 57.1% agreeable. In Total looks the test results of model I respondents said 42.8% very good, 57.1% good, test results of model II respondents said 42.8% very good and 57.1% good and test results model III respondents said 57.1 % very good and 42.8% good